Surface ozone variations at the Great Wall Station, Antarctica during austral summer - Justin Sentian; Franky Herman; Mohd Sharul; Vivian Kong (2020)
Surface ozone (O3) is a secondary pollutant harmful to human health and a greenhouse gas which is one of the prime climate forcers. Due to the clean atmospheric environment of the Antarctic region and given the complexity of O3 chemistry, the observation of surface O3 variability in this region is necessary in the quest to better understand the potential sources and sink of polar surface O3. In this paper, we highlighted our observations on O3 variability at the Great Wall Station (GWS) during austral summer in December 2018 and January 2019. The continuous surface O3 measurement at the GWS, Antarctica was carried out using the Ecotech Ozone analyzer. To understand the roles of the meteorological conditions on the temporal variations of O3, meteorological data was obtained from the conventional auto-observational station at the GWS. The Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model was employed to investigate the air mass transport over the region. The observed austral summer surface O3 concentrations at the GWS exhibited variability and were significantly lower than those previously observed at other permanent coastal stations in Antarctica. The surface ozone variability at the GWS was strongly influenced by the synoptic change of air mass origin although the roles of photochemistry production and destruction were still uncertain. Marine characteristics and stable surface O3 characterized the air masses that reached the GWS. The unique characteristic of surface O3 at the coastal site of GWS was emphasized by its synoptic air mass characteristics, which displayed a significant influence on surface O3 variability. Air mass that traveled over the ocean with relatively shorter distance was linked to the lower O3 level, whereby the marine transport of reactive bromine (Br) species was thought to play a significant role in the tropospheric chemistry that leads to O3 destruction. Meanwhile, the diurnal variation indicated that the O3 background concentration levels were not strongly associated with the local atmospheric conditions.